2012
DOI: 10.3174/ajnr.a3369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theApolipoprotein Eε4 Allele on Functional MRI duringn-Back Working Memory Tasks in Healthy Middle-Aged Adults

Abstract: BACKGROUND AND PURPOSE:APOE4 is the best-documented genetic risk factor for sporadic AD. Previous research showed that APOE4 is associated with increased risk of occurrence and earlier onset of AD in a gene dose-dependent manner. However, the specific role of APOE4 in processing of brain functions requires further investigation. Investigators have used fMRI to measure brain activity on the basis of the blood oxygen level-dependent contrast. This study investigates the effects of APOE4 on fMRI during n-back WM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
(35 reference statements)
3
20
1
Order By: Relevance
“…Thus, while supporting Aβ-related hyperactivation previously observed in cognitively normal elderly, the present results provide the novel finding of Aβ-related hyperactivation beyond the MTL-based EM network. These results are consistent with a growing field of research examining the impact of known risk factors in prodromal AD, such as ApoE4 allele, to frontoparietal function and cognitive control (Chen, et al, 2013, Wishart, et al, 2006). …”
Section: Discussionsupporting
confidence: 88%
“…Thus, while supporting Aβ-related hyperactivation previously observed in cognitively normal elderly, the present results provide the novel finding of Aβ-related hyperactivation beyond the MTL-based EM network. These results are consistent with a growing field of research examining the impact of known risk factors in prodromal AD, such as ApoE4 allele, to frontoparietal function and cognitive control (Chen, et al, 2013, Wishart, et al, 2006). …”
Section: Discussionsupporting
confidence: 88%
“…Although early and significant episodic memory impairment constitutes the clinical core diagnostic criterion of AD (Dubois et al, 2014), there is increasing evidence of early deficits in WM and executive function in patients with MCI and AD (Crawford et al, 2013;Gagnon and Belleville, 2011;Huntley and Howard, 2010;Kessels et al, 2011;Koppel et al, 2014). Moreover, fMRI studies have also suggested a possible subclinical impairment of WM capacity in healthy APOE ε4 carriers (Chen et al, 2013). Here, we investigated the effects of BIN1 rs744373 on the performance of n-back WM tasks in young healthy individuals.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the T2DM patients had few additional resources available in the highload conditions and, thus, exhibited a significant correlation between the SFG impairments and cognitive processes. We have previously found some evidence from an examination of the effect of APOE4, the strongest genetic risk factor for AD, on brain activation in response to different WM loads (45).…”
Section: Discussionmentioning
confidence: 99%